2010
DOI: 10.1161/circimaging.109.854307
|View full text |Cite
|
Sign up to set email alerts
|

Iodinated Contrast Opacification Gradients in Normal Coronary Arteries Imaged With Prospectively ECG-Gated Single Heart Beat 320-Detector Row Computed Tomography

Abstract: Background-To define and evaluate coronary contrast opacification gradients using prospectively ECG-gated single heart beat 320-detector row coronary angiography (CTA). Methods and Results-Thirty-six patients with normal coronary arteries determined by 320ϫ0.5-mm detector row coronary CTA were retrospectively evaluated with customized image postprocessing software to measure Hounsfield Units at 1-mm intervals orthogonal to the artery center line. Linear regression determined correlation between mean Hounsfield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
99
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(108 citation statements)
references
References 11 publications
8
99
0
1
Order By: Relevance
“…TAG is a novel method developed to assess the hemodynamic significance of CAD and is calculated using a linear regression model of luminal contrast attenuations in a coronary vessel obtained by manual or semi-automated techniques [9,10,[19][20][21][22]. To date, several studies have examined the relation of TAG to invasive FFR and have shown a variety in the diagnostic accuracy of TAG in predicting lesion-specific ischemia by invasive FFR \0.80.…”
Section: Discussionmentioning
confidence: 99%
“…TAG is a novel method developed to assess the hemodynamic significance of CAD and is calculated using a linear regression model of luminal contrast attenuations in a coronary vessel obtained by manual or semi-automated techniques [9,10,[19][20][21][22]. To date, several studies have examined the relation of TAG to invasive FFR and have shown a variety in the diagnostic accuracy of TAG in predicting lesion-specific ischemia by invasive FFR \0.80.…”
Section: Discussionmentioning
confidence: 99%
“…Wide-volume scanners with 320 detector rows and up to 16 cm of cranial-caudal coverage enable wholeheart coverage at one acquisition time point (within one heartbeat or volume), which eliminates "stair-step" or misalignment artifacts (11)(12)(13) but also permits uniform attenuation when evaluating the coronary arteries, when analyzing myocardial perfusion defects (14,15), or when measuring contrast attenuation gradients across atherosclerotic lesions (16). Radiation doses are lower with wide-area detector scanners owing to shorter scanning times and reduction of redundant radiation from either overlapping of sequential axial scans or helical oversampling (13).…”
Section: Methodsmentioning
confidence: 99%
“…and heart rates at lower radiation doses compared with previous-generation CT scanners. This technology could further facilitate CT stress perfusion (14,15), contrast attnenuation gradients across atherosclerotic lesions (16), and noninvasive fractional flow reserve computed from coronary CT angiography (39).…”
Section: Cardiac Imaging: Submillisievert Radiation Dose For Coronarymentioning
confidence: 99%
“…This method is based on the assumption that the HU value (intensity) along the artery should be a smooth gradual decreasing curve when this artery is without the presence of calcium [16].…”
Section: Centerline Extractionmentioning
confidence: 99%